Translingual Practice Involving a Local Dialect and a Local Language in an EFL Classroom: A Case Study of a Public Junior High School in Brebes District - Ayu Ida Savitri; Sisilia Setiawati Halimi; Harni Kartika Ningsih (Master Program in Linguistics, Diponegoro University, 2026)
Implementing translingual practices that involve foreign, national, and local languages in EFL classrooms remains challenging for many EFL teachers. Close observation of teachers’ actual classroom implementation is thus necessary to better understand how such practices are enacted. This study aims to show how translingual practice is done by a teacher using a local dialect and how different languages construct meaning during her teaching in the classroom interactions. The study employed a qualitative approach to examine the teacher’s translingual practice, specifically using Canagarajah’s (2013) negotiation strategies. The participants were thirty Grade 7 students and an English teacher at a public junior high school in the Brebes District. The data were drawn from three lessons of classroom interactions before the final-year assessment. The results showed that the teacher used English, Indonesian, Javanese, and Javanese in Brebes Dialect to support the students’ EFL learning. They are used for constructing meaning in classroom interactions by elaborating Envoicing, Recontextualization, and Interaction negotiation strategies.